Tensile Properties and Microstructures of a 2024-T351 Aluminum Alloy Subjected to Cryogenic Treatment - Jianzhong Zhou; Suqiang Xu; Shu Huang; Xiankai Meng; Jie Sheng; Haifeng Zhang; Jing Li; Yunhui Sun; Emmanuel Agyenim Boateng (Metals, 2016)
The aim of this study was to investigate the effects of the cryogenic treatment (CT) using liquid nitrogen on tensile properties and microstructures of the 2024-T351 aluminum alloy. Tensile tests were carried out, and tensile fractures were observed using a scanning electron microscope (SEM). The microstructure evolution of 2024-T351 subjected to CT was also studied using both an optic microscope (OM) and a SEM. The components of the second phase were tested with an energy dispersive spectrometer (EDS). The results showed that both the ultimate strength and the yield strength of the 2024-T351 aluminum alloy could be improved through CT without the sacrifice of elongation. In addition, tensile fractures showed that the plasticity of 2024-T351 aluminum might also be improved, as the dimples in the fracture of the CTed specimens were markedly more uniform compared with the untreated specimen. The phenomenon of grains refinement (GR) was found through microstructure observation. It was also found that the second phases were distributed more uniformly after CT. A conceivable mechanism concerning the shrinking effect and crystal grain movement was raised to explain the experimental phenomena. The effects of CT on residual stress in the 2024-T351 aluminum alloy are discussed herein. Measurements showed that tensile residual stress in 2024-T351 was removed, and slight compressive residual stress was generated after CT. This may also contribute to the improvement of the tensile properties of the alloy.